Influence of microorganism and plant oils on the structure of mannosylerythritol lipid (MEL) biosurfactants revealed by a novel thin layer chromatography mass spectrometry method. (1st August 2019) - Beck, Alexander; Haitz, Fabian; Grunwald, Saskia; Preuss, Laura; Rupp, Steffen; Zibek, Susanne
Abstract: Mannosylerythritol lipids (MEL) are microbial glycolipid biosurfactants with great potential for application in cosmetics and household detergents. In current biotechnological processes, they are produced by basidiomycetous fungi, the Ustilaginaceae, as a complex mixture of different chemical structures. It was the aim of this paper to study the influence of producer organisms and substrates on the resulting MEL structures with a novel high-resolution HPTLC–MALDI-TOF method. Given the seven different microbes and four plant oils, our analysis revealed that the product concentrations varied strongly between organisms, while they were similar for the different substrates. Coconut oil presented an exception, since only one organism was able to synthesize MEL from this substrate in considerable yields. Analysis by GC-FID further showed that the chain length pattern of hydrophobic fatty acid side-chains was very specific for individual organisms, while substrates had only a minor influence on the chain length. Our novel HPTLC–MALDI-TOF combination method finally demonstrated the presence of multiple MEL sub-variants with differing acetylation and fatty acid chain lengths. It also revealed the production of a more hydrophilic biosurfactant mannosylmannitol lipid (MML) as a side-product in certain fungi. Overall, it was concluded that the pattern of produced biosurfactant structures are mainly governed by producer organisms rather than substrates.